STUDY OF MICROBIOLOGICALLY INFLUENCED CORROSION IN ALUMINUM BY SULFATE-REDUCING BACTERIA IN SEAWATER USING IMERSION, POLARIZATION, AND ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY METHOD - KHALIDA LUKMAN, INTAN
#DESCRIPTION_ALTERNATIVE#